(untitled) (Physical Education, Health and Social Sciences, 2025)
English teachers work in different ways to play an active role in classroom-based oral development activities. This study will examine the use of picture description as a strategy to develop and enhance analytical thinking and communication skills among the secondary school students in district Mardan. The research model will be qualitative and will be adopted from the theory of semiotics. Data will be collected from 60 selected students of secondary school based on group tests and focused group interview. This study will show the need for picture insertion in English text books.